Pletivo života: Teologicko-misiologické implikácie jednej metafory - Pavol Bargár (Teologická Reflexe)
One of the major insights drawn from anthropological research is the acknowledgment that every human being is in each stage of their life embedded in a complex and multi-layered structure of relationships with other people as well as the world around them. Furthermore, theologically rooted anthropologies accentuate yet another type of relationship, namely, one between a human being and the transcendent reality that has in Christian tradition been referred to as God. Following from this fundamental point of departure this article seeks to explore two main questions. First, in which ways can one theologically-missiologically reflect on human existence? And second, what theological-missiological implications does such reflection have? The article proposes the metaphor of a web of life as one possible image that has the potential to inform and orientate such exploration.